Education as a Genuine Social and Personal Value - Machynska, Nataliya; Derkach, Yuliya (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
Education is considered to play the role of social institution which transmits basic cultural values and goals of society. It helps to create new things not forgetting about the old ones. The process of education turns and directs the life of society, saving even of the smallest value to humans. Education has the capacity to design individual skills and values, to increase the mobility of the individual in society being the main source of forming a certain system of human values. A person who is able to live effectively and work in a global environment should be prepared by education. Education as a personal value is displayed through the implementation of tasks of patriotic education, which is important because of a sense of belonging to a nation and state. In order the education to become valuable for everybody, it is necessary it to give the key knowledge. To encourage a new generation of independent, individual learning, that will reflect in the desire to do something and to create something